PERAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) ' DALAM MENANGANI KONFLIK PENDIRIAN RUMAH IBADAH - Ardiansyah Ardiansyah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
Dialogue among people gets religion help to increase collaboration among its follower. Ala thus goes together we can uphold humanitarianism, justice, peace, and brotherhood Dialogue will settle competition, grind, dislike, creating harmony and keeps away life attitude that mutually destroys. This in the context, interfaith dialogue can be done in various form, as dialogue of life, social job dialogue, dialogue among monastik, dialogue for do 'a with (istighosah), and teologis's discussion dialogue